Applied sport mechanics - Burkett, B. (Human Kinetics, 2019)
Applied Sport Mechanics, Fourth Edition With Web Resource, helps undergraduate students understand how the fundamental laws of human movement affect athletes` performances. Foundational principles of kinetics, kinematics, and sports technique are clearly presented and then explored through a variety of applied scenarios.